Mechanistic Insights into the Adenosine A1 Receptor’s Positive Allosteric Modulation for Non-Opioid Analgesics - Tal Weizmann; Abigail Pearce; Peter Griffin; Achille Schild; Maren Flaßhoff; Philipp Grossenbacher; Martin Lochner; Christopher A. Reynolds; Graham Ladds; Giuseppe Deganutti (Cells)
The adenosine A1 receptor (A1R) is a promising target for pain treatment. However, the development of therapeutic agonists is hampered by adverse effects, mainly including sedation, bradycardia, hypotension, or respiratory depression. Recently discovered molecules able to overcome this impediment are the positive allosteric modulator MIPS521 and the A1R-selective agonist BnOCPA, which are both potent and powerful analgesics with fewer side effects. While BnOCPA directly activates the A1R from the canonical orthosteric site, MIPS521 binds to an allosteric site, acting in concert with orthosteric adenosine and tuning its pharmacology. Given their overlapping profile in pain models but distinct mechanisms of action, we combined pharmacology and microsecond molecular dynamics simulations to address MIPS521 and BnOCPA activity and their reciprocal influence when bound to the A1R. We show that MIPS521 changes adenosine and BnOCPA G protein selectivity in opposite ways and propose a structural model where TM7 dynamics are differently affected and involved in the G protein preferences of adenosine and BnOCPA.